Increased inhibition of cytochrome P450 3A4 with the tablet formulation of posaconazole. Issue 5 (October 2016) - Petitcollin, A.; Crochette, R.; Tron, C.; Verdier, M.-C.; Boglione-Kerrien, C.; Vigneau, C.; Bellissant, E.; Lemaitre, F.
Abstract: Being a substrate of the cytochrome P450 3A4 (CYP3A4) isoenzyme, sirolimus metabolism is decreased when posaconazole is administered concomitantly. However, because of the poor bioavailability of the oral suspension of posaconazole with which low plasma concentrations are obtained, CYP3A4 inhibition is weak and a 50–75% dose reduction of sirolimus is sufficient to avoid sirolimus overdosage. The new tablet formulation allows reaching posaconazole concentrations 3–4 fold higher than those obtained with the oral suspension. Based on a case of sirolimus overdosage following posaconazole tablets administration, we modelled the inhibition of sirolimus clearance by posaconazole, and then simulated several dosage regimens of sirolimus taken together with posaconazole tablets. We were able to describe well the interaction, and found a value of IC50 of posaconazole towards sirolimus clearance of 0.68 μg/mL. The simulations showed that even a 80% decrease of the daily dose of sirolimus is unsuitable in many cases with trough concentrations of posaconazole of 2 μg/mL. A decrease of 40% of the dose with spacing administrations of 3 days may be considered. The clinicians and pharmacologists must be warned that the use of posaconazole tablets may result in an inhibition of CYP3A4 of greater magnitude than with the oral suspension.